KESEHATAN KERJA DAN KONSUMSI GIZI PADA MARBOT MASJID/MUSHOLLA DI WILAYAH KELURAHAN TANGKERANG SELATAN - Hasrianto, Nofri; Mayasari, Eva; Hayu, Riska Epina; Randika, Rendi; Redho, Ahmad (Devote: Jurnal Pengabdian Masyarakat Global, 2023)
Healthy living and carrying out the work of Mosque and Prayer Room Gharim/marbots is very important because Gharim/Marbots interact with the congregation. Comfort in worship is a priority, especially personal hygiene. This Community Service aims to provide education regarding personal hygiene patterns and work implementation carried out by Gharim/marbot. The service activities went well and smoothly, but only 20% of the Gharim/Marbot were able to attend and take part in the educational activities. The activity went well and the enthusiasm of the training participants was very visible by actively asking questions and providing answers to questions asked by the presenters and discussions about health and carrying out work. Before carrying out community service, a pretest was carried out, namely asking each participant about occupational health and knowledge about nutritional consumption. The method of implementing the activity is to provide knowledge/education to all gharim and marbot of mosques and prayer rooms in the working area of Tangkerang Selatan sub-district. This activity was carried out in the Village Building Hall, supported by village officials and the head of the RW RT in the Tangkerang Selatan. From the results of providing